2022
DOI: 10.1177/09722629221087386
|View full text |Cite
|
Sign up to set email alerts
|

Overreaction, Investor Sentiment and Market Sentiment of COVID-19

Abstract: This study examines the impact of investor sentiment and market sentiment on overreaction in Europe and USA markets before and during COVID-19. The investor sentiment is calculated by the standard deviation, realized volatility, Parkinson’s estimator and Garman and Klass’s estimator. The market sentiment is measured by Business Confidence Index, Consumer Confidence Index, Labour Force Survey, Leading Index and Monetary Aggregates. The results of this study show that investor and market sentiments are correlate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…The extensive influence of COVID-19 globally illustrates the wide-ranging effects of a significant societal event, either directly or indirectly. Many studies have confirmed the direct or indirect effects of COVID-19 on financial markets and investor sentiment (Goel and Dash 2022;Loang 2022). These effects are likely to result in changes to the integrity factor, subsequently affecting the outcomes of the game of lies among investors on social media.…”
Section: (6) If = Pearson(is Sm)mentioning
confidence: 95%
“…The extensive influence of COVID-19 globally illustrates the wide-ranging effects of a significant societal event, either directly or indirectly. Many studies have confirmed the direct or indirect effects of COVID-19 on financial markets and investor sentiment (Goel and Dash 2022;Loang 2022). These effects are likely to result in changes to the integrity factor, subsequently affecting the outcomes of the game of lies among investors on social media.…”
Section: (6) If = Pearson(is Sm)mentioning
confidence: 95%
“…[29] examined the role of trading volume and volatility in the Russian stock market. [32] measured the investor sentiment by different metrics of volatility: the standard deviation, realized volatility, Parkinson's estimator and Garman and Klass's estimator. The author revealed that realized volatility is the only investor sentiment indicator that significantly impacts on stock returns with the emergence of COVID-19 in the EU and US markets.…”
Section: Literature Review and The Hypotheses Of The Studymentioning
confidence: 99%
“…Trading volume [4,15,28,31] Extreme past returns [4,15] Volatility [32,51] Intensity of web search queries for companies (in Google, Wikipedia, etc.) [15,16] Survey sentiment indicators [14] The tone of messages in social networks [14,36,41] Divergence of investor opinion [13] Author-developed indices based on the tone of investor messages and divergence of opinion (Bull-Bear Spread, Bullishness Index, Agreement Index, Variation of Bullish Ratio, etc.)…”
Section: Attention and Sentiment Metrics Source Articlementioning
confidence: 99%